Pembelajaran Kepada Masyarakat Kelurahan Lamaru RT 06 Dan RT 17 Untuk Meningkatkan Daya Minat Belajar - Ganjar Susilo; Prita Indriawati; Retnowaty Retnowaty (Abdimas Universal, 2019)
Learning activities for the community in the villages of Lamaru RT 06 and RT 17 were Community Service activities carried out by lecturers and students at the University of Balikpapan in Lamaru Village, East Balikpapan, with the aim of realizing the Tri Dharma of Universities by using their values and forms in community and state life, increase the power of interest in learning society in order to get a better education and provide new insights and knowledge about education and can be used in community life in the area where local people live. The method of community service in RT 17 and RT 06 of Lamaru Village by conducting Focus Group Discussions (FGD). The results of the discussion were 1) the formation of cooperation between the community service team of the University of Balikpapan very well so that efforts to increase the learning interest of the community in Lamaru Sub-District can run well, 2) the students who took part in educational activities were very active in the activities given, such as tutoring, knowledge dexterity competitions, and simple experiments in setting up model patterns of objects around them using plasticine media, and 3) young people playing an active role in helping education skills in creative activities. Keywords: community learning interest, tutoring, knowledge agility competition